The general epistle of James an introduction and commentary - Tasker, R.V.G. (London, UK Tyndale, 1956)
Includes bibliographical references.
In 1957, this volume was included in the Tyndale New testament Commentary series. Donated by Mr G. Wells, student 1960.
Keywords: Bible. N.T. James -- commentaries